2020
DOI: 10.1016/j.ijnss.2020.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Unplanned hospital readmissions after kidney transplantation among patients in Hefei, China: Incidence, causes and risk factors

Abstract: Objectives Unplanned readmissions severely affect a patient’s physical and mental well-being after kidney transplantation (KT), which is also independently associated with morbidity. A retrospective study was conducted to identify the incidence, causes and risk factors for unplanned readmission after KT among Chinese patients. Methods Patients who underwent KT were admitted to the organ transplant center of the Affiliated Hospital of University of Science and Technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
3
5
0
1
Order By: Relevance
“…Third, although dexmedetomidine may reduce the length of hospital stay after kidney transplant, 13 we did not observe such an effect. The median length of hospital stay of 25 days in this trial was in line with the data originated in China 46 , 47 but appeared much longer than that in the US and European countries. 48 , 49 , 50 This difference may be attributed to the different health care systems in various countries.…”
Section: Discussionsupporting
confidence: 87%
“…Third, although dexmedetomidine may reduce the length of hospital stay after kidney transplant, 13 we did not observe such an effect. The median length of hospital stay of 25 days in this trial was in line with the data originated in China 46 , 47 but appeared much longer than that in the US and European countries. 48 , 49 , 50 This difference may be attributed to the different health care systems in various countries.…”
Section: Discussionsupporting
confidence: 87%
“…Contrary to this, McAdams et al [8] found that women with diabetes had a higher risk of 30 days' readmission than men with diabetes. Factors at the time of transplant that were found to be associated with the increased hospital readmission in different studies [8,14,15,[21][22][23] are older age, higher body mass index (BMI), diabetes mellitus, a history of heart disease or chronic obstructive pulmonary disease, expanded criteria deceased donor (vs. living donor), use of an induction agent, any degree of human leukocyte antigens matches, longer mean length of stay (LOS) for the transplant hospitalization, being discharged on the weekend, frailty, median time on dialysis, being transplanted preemptively rather than having had conventional hemodialysis, and dialysis modality. However, these associations were not reproduced in the following studies.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 81.1% of patients were readmitted after LRRT within the first six months, with 43.4% admitted within 30 days and 62.5% within three months. A study from China [ 14 ] showed a readmission rate of 22.59% within one year after KT while data from the United States Renal Data System (USRDS) showed 31% (range from 18% to 47% among different transplant centres) of recipients readmitted within 30 days of discharge after KT [ 8 ]. A study from Canada [ 15 ] found early readmission rates of 19.4% at 30 days and 26.8% at 90 days post-transplant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Los procesos infecciosos, rechazo agudo y la insuficiencia renal postrasplante renal, son los motivos principales para un reingreso hospitalario, posterior a los 30 días que se le haya dado el alta al paciente, aumentando la morbilidad y mortalidad en un 50% (49). Los reingresos hospitalarios posterior alta médica no solo afecta al injerto, sino que también se ve afectada la economía, salud mental y los recursos hospitalarios puesto que para ellos también representa una carga (50).…”
Section: Journal Scientific Mqrinvestigar 3352unclassified